Measles prevention and control in the acute healthcare setting—minding the gaps - Loreen Herwaldt; Hilary Babcock; Karen Brust; Susan E. Beekmann; Philip Polgreen (Infection Control & Hospital Epidemiology, 2026)
Abstract Background: As measles vaccination rates in the United States decline and incidence rises, healthcare facilities face an increased risk of measles transmission. Measles exposures in clinical settings lead to extensive contact tracing investigations, significant staffing disruptions, high costs, and potential infections in vulnerable patients. This study aimed to assess US hospitals’ readiness of to identify and manage measles exposures and to identify common infection prevention gaps. Methods: In 2025, the Emerging Infections Network (EIN) conducted a 9-question electronic survey of its physician members. The questions addressed immunization policies, exposure identification capabilities, and management protocols. Results: Of 153 respondents whose scope of practice includes measles prevention, 139 (91%) reported that their institutions required evidence of measles immunity for some healthcare personnel; 20% applied this requirement to a subset. Only 36% of facilities stored immunity data for employed staff in accessible electronic format. Most facilities could determine when patients were in specific clinical areas but could not identify visitors or non-employed staff. Exposure definitions varied; 33% of respondents used criteria that potentially underestimate exposure risk (eg, >15 min of shared air). Others lacked access to air exchange data (33%). Furthermore, 12%–31% of respondents reported their institutions do not consistently recommend postexposure prophylaxis for non-immune individuals. Conclusions: Despite the high transmissibility of measles, significant gaps in record-keeping, exposure definitions, and prophylaxis protocols persist in US hospitals. Standardized exposure criteria and improved accessibility to staff immunity records could help reduce measles transmission in health care and the associated clinical and financial adverse outcomes.